Overcoming Barriers to Applying Systems Thinking Mental Models in Policy-Making; Comment on "What Can Policy-Makers Get Out of Systems Thinking? Policy Partners' Experiences of a Systems-Focused Research Collaboration in Preventive Health" - Sobia Khan (Kerman University of Medical Sciences, 2021)
Systems thinking provides the health system with important theories, models and approaches to understanding and assessing complexity. However, the utility and application of systems thinking for solution-generation and decision-making is uncertain at best, particularly amongst health policy-makers. This commentary aims to elaborate on key themes discussed by Haynes and colleagues in their study exploring policy-makers' perceptions of an Australian researcher-policy-maker partnership focused on applications of systems thinking. Findings suggest that policy-makers perceive systems thinking as too theoretical and not actionable, and that the value of systems thinking can be gleaned from greater involvement of policy-makers in research (ie, through co-production). This commentary focuses on the idea that systems thinking is a mental model that, contrary to researchers' beliefs, may be closely aligned with policy-makers' existing worldviews, which can enhance adoption of this mental model. However, wider application of systems thinking beyond research requires addressing multiple barriers faced by policy-makers related to their capability, opportunity and motivation to action their systems thinking mental models. To make systems thinking applicable to the policy sphere, multiple approaches are required that focus on capacity building, and a shift in shared mental models (or the ideas and institutions that govern policy-making).